Factors influencing a child's development in the early years of life and their impact on adulthood - Magdalena Joanna Czeczotka; Marta Skorupska; Martyna Magdalena Martka; Natalia Aleksandra Popławska; Justyna Śliz; Krzysztof Woźniak (Nicolaus Copernicus University in Toruń, 2024)
Introduction:   This article reviews a number of studies that have sought to determine how factors that occur in prenatal life and early childhood may lead to psychiatric disorders in adulthood. It focuses on the relationships between the physiology and pathophysiology of the autonomic nervous system and their impact on the child's development, on previously experienced traumas, on living in unfavorable conditions, on factors that have a negative impact on the fetus during pregnancy, and on the existence of two psychopathological dimensions and their connections with specific psychiatric disorders.   Aim of study:   The aim of the study is to present a comprehensive review of some of the most common forms of childhood maltreatment and show how powerful the impact they have on children's development and their later adult life.     Materials and methods:   Materials used in this study were found in the PubMed database, using the following keywords: childhood maltreatment, sexual abuse, physical abuse, mental abuse, alcohol and drug abuse, and psychiatric disorders.   Conclusion:   The work clearly shows that neglect, abuse, and abnormal behavior have a direct impact on psychiatric disorders occurring in children and on the consequences that children have to bear as a result of their adult lives.